Transmission of Viruses from Wild Animals to Humans, a Solution by Applying Syari’ah Rules and Regulations toward Animals - Islam, Md Monzurul (Halalsphere, 2022)
Humans are inevitably dependent on animals for their daily life. Animals contribute significantly to the human food cycle, yet simultaneously, it causes many diseases in the human body by transmitting hazardous viruses and pathogens to humans. The recent outbreak of COVID-19 is considered the outcome of taking the meat of some animals that transmitted the virus to human bodies. Since it is impossible to avoid meat entirely because of humans’ food habits and meeting the demand for protein, a solution should be developed to save humans from getting affected by the transmitted virus and pathogens. This study mainly focuses on reducing the possibility of such an outbreak as COVID-19 due to some wild animals’ consumption. Hence, this study proposes Shari’ah principles and legal maxims as a possible preventive measure. This study shows that many prohibited animals, according to Islam, are the reservoirs of viruses and pathogens. Therefore, sorting out suitable animals based on Shari’ah principles and legal maxims can save humans from getting affected by these transmitted viruses.